2006
DOI: 10.1021/je060291c
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Determination of Thermophysical Properties and Critical Parameters for the Mixture (51 wt % R143a + 49 wt % R125) and Critical Line of xCO2 + (1 − x)(51 wt % R143a + 49 wt % R125)

Abstract: The thermophysical properties and critical parameters for the alternative refrigerant (51 wt % of 1,1,1-trifluoroethane (R143a) + 49 wt % of pentafluoroethane (R125))svery close to the composition of R507 (50 wt % of each mixture component)swere investigated using two different acoustic techniques. The critical behavior of the system xCO 2 + (1x)(51 wt % R143a + 49 wt % R125) was also investigated. Experimental data of speed of sound in liquid (51 wt % R143a + 49 wt % R125) from T ) (253 to 338) K and pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Dzida and co-workers have studied u(T,P) for n-alkanes, alcohols and their mixtures, and have discussed their results from a physical chemistry point of view. The research groups of Lago et al, [91][92][93][94][95][96][97][98][99][100] Kabelac et al, [101][102][103][104] Guedes et al, [106][107][108][109] Trusler et al [110][111][112] and others 105,113,114 have reported measurements of u(T,P) on compounds such as: water, hydrocarbons, refrigerants, oils over a wide range of temperature and pressure. Research on the u(T,P) for biomassderived fuels and related compounds has recently been reported.…”
Section: Speed Of Sound In Liquid Organic Compoundsmentioning
confidence: 99%
“…Dzida and co-workers have studied u(T,P) for n-alkanes, alcohols and their mixtures, and have discussed their results from a physical chemistry point of view. The research groups of Lago et al, [91][92][93][94][95][96][97][98][99][100] Kabelac et al, [101][102][103][104] Guedes et al, [106][107][108][109] Trusler et al [110][111][112] and others 105,113,114 have reported measurements of u(T,P) on compounds such as: water, hydrocarbons, refrigerants, oils over a wide range of temperature and pressure. Research on the u(T,P) for biomassderived fuels and related compounds has recently been reported.…”
Section: Speed Of Sound In Liquid Organic Compoundsmentioning
confidence: 99%